Equilibrium exchange rates in oil-dependent countries - Iikka Korhonen; Tuuli Juurikkala (Bank of Finland, Institute for Economies in Transition (BOFIT), 2007)
We assess the determinants of equilibrium real exchange rates in a sample of oil-dependent countries.Our basic data cover OPEC countries from 1975 to 2005.We also include three oil-producing Commonwealth of Independent States (CIS) countries in our robustness analysis.Utilising several estimation techniques, including pooled mean group and mean group estimators, we find that the price of oil has a clear, statistically significant effect on real exchange rates in our group of oil-producing countries.Higher oil price lead to appreciation of the real exchange rate. Elasticity of the real exchange rate with respect to the oil price is typically between 0.4 and 0.5, but may be larger depending on the specification.Real per capita GDP, on the other hand, does not appear to have a clear effect on real exchange rate.This latter result contrasts starkly with the consensus view of real exchange rates determinants, emphasising the unique position of oil-dependent countries.
URN:NBN:fi:bof-201408072019
Keywords: F31; F41; P24; Q43; 330; equilibrium exchange rate; pooled mean group estimator; resource dependency